2016
DOI: 10.1007/s12035-016-0050-9
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Coupling Between Functional Connectivity Density and Amplitude of Low Frequency Fluctuation in Non-Neuropsychiatric Systemic Lupus Erythematosus: a Resting-Stage Functional MRI Study

Abstract: In this study, we seek to explore alterations of coupling between functional connectivity density (FCD) and amplitude of low frequency fluctuation (ALFF) in systemic lupus erythematosus patients without overt neuropsychiatric symptoms (non-NPSLE) by using resting-state functional MR imaging. This study was approved by the institutional ethical review board, and all participants signed written informed consent prior to the study. Twenty six non-NPSLE patients and 35 matched healthy controls underwent resting-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 45 publications
4
24
0
Order By: Relevance
“…CBF significantly increased in GM in the temporal gyrus, cingulate gyrus, and cerebellum regions and in widespread WM in non‐NPSLE patients compared with NCs. We hypothesized that this result may be caused by a compensatory mechanism in response to ischemia or injury, which was consistent with previous fMRI studies showing hyperactivities and hyperconnectivity within certain specific networks (e.g., the sensorimotor network) (Mikdashi, ; Niu et al, ; Nystedt et al, ; Papadaki et al, ; Wu et al, ; Zhang et al, ). However, in NPSLE patients, along with widespread vasculopathy and thrombosis, the perfusion of these brain regions was significantly decreased, which means a large reduction in compensatory capacity when the damage exceeded the threshold.…”
Section: Discussionsupporting
confidence: 86%
“…CBF significantly increased in GM in the temporal gyrus, cingulate gyrus, and cerebellum regions and in widespread WM in non‐NPSLE patients compared with NCs. We hypothesized that this result may be caused by a compensatory mechanism in response to ischemia or injury, which was consistent with previous fMRI studies showing hyperactivities and hyperconnectivity within certain specific networks (e.g., the sensorimotor network) (Mikdashi, ; Niu et al, ; Nystedt et al, ; Papadaki et al, ; Wu et al, ; Zhang et al, ). However, in NPSLE patients, along with widespread vasculopathy and thrombosis, the perfusion of these brain regions was significantly decreased, which means a large reduction in compensatory capacity when the damage exceeded the threshold.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the coupling between ALFF and FCDs could comprehensively and synergistically expose the dysfunction in patients with IGE and its subgroups. Based on previous studies ( 11 , 20 ), Pearson correlation was used to evaluate the coupling between ALFF and FCDs. The Pearson correlations between ALFF and FCDs were calculated both voxel-wise and subject-wise in the gray matter mask which was generated by averaging the gray matter segmentations of T1 weight scans from all subjects ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…These studies separately revealed changes in ALFF and FCD in patients with IGE. Recent evidence indicated that combining ALFF and FCD might improve the capability for focusing detection and comprehensively revealing the intrinsic brain network dysfunction ( 11 , 20 ), although a specific neuronal processes is difficult to find to match the coupling between two resting state features. The decreased coupling of amplitude and connectivity in mesial temporal regions and increased coupling in posterior regions of the DMN have been revealed in patients with temporal lobe epilepsy ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies indicated that low-frequency restingstate fMRI activity, as quanti ed by amplitude of low-frequency uctuations(ALFF) or fractional ALFF (fALFF) suited to measure the cognition capability [7] [8], but it remains unclear whether the dynamic patterns of ALFF or fALFF is relevant to cognitive decline. Although evidence has shown that regional spontaneous neural activity related closely to FC [9][10], we have little knowledge about the relationship between dynamic patterns of ALFF/fALFF and FC and whether the relationship is linked to cognitive decline.…”
Section: Introductionmentioning
confidence: 99%